Toxicological implications of Margaritaria discoidea aqueous seed extract on Na+, K+-ATPase specific activity, glucose and serum electrolytes level in wistar rats - Onyeabo, Chimaraoke; Nnacheta, Polycarp (International Journal of Pharmacology and Toxicology, 2016)
The effect of aqueous seed extract of Margaritaria discoidea on Na+ K+ ATPase activity and toxicity studies of its seed extract were investigated in albino rats. The study involved oral administration of different doses of the aqueous extract to groups of male albino rats at 25, 50,100, and 200mg/kg body weight resulted in significant (p<0.05) decrease in sodium, potassium and glucose levels while chloride and calcium ions showed a significant (p<0.05) increase relative to control. The seed extract also showed significant (p<0.05) decrease in Na+ K+ ATPase specific activity in a dose dependent manner relative to control. The median lethal dose (LD50) of this extract in mice was established at 316.2mg/kg body weight using probit of mortality. The results showed that the acute toxicity potency of the aqueous extract of the seeds was practically non-toxic. The study showed that seeds of Margaritaria discoidea could be toxic if not consumed in moderate quantities.